THE EVALUATION OF IRANIAN-AMERICAN RELATIONS DURING TRUMP’S REGIME 2016-2020 & ITS IMPLICATION FOR THE MIDDLE EAST, SYRIA- CASE STUDY - Nidal Abed Mahmood, Sabah Jaber Kadhem AL Dulaimi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In this research, a discussion is provided on Iranian & American relations under trumps regime, and its implication for Middle East & Syria. In the study, several implications & diplomatic relations between the countries have been evaluated. Iran reacted to the America most extreme weight battle under part through showing its capacity to hurt worldwide business & other America interests & to raise worries about Iranian’s atomic exercises. Iran may have tried to cause universal on-screen characters, including those that rely upon stable oil supplies, to force the Trump Administration to decrease its assents pressure on Iran. An exertion through America to implement EU sanctions against Syria opened up a question between Iranian & America. On July 4, specialists from the British Overseas Territory Gibraltar, sponsored through British marines, seized an Iranian tanker, the Grace I, off the bank of Gibraltar under light of the fact that it was purportedly damaging an EU ban on the arrangement of oil to Syria. Iranian authorities criticized the seizure and referred to is as a demonstration of theft, and subsequently, the IRGC Navy tried to catch an America claimed tanker under the Gulf, the British Heritage. However, the power was supposedly passed off through a British warship.